Kajian Perancangan Logo Kelompok Sadar Wisata Gatari Mass Sebagai Salah Satu Destinasi Wisata Alam Baru - Christofer Satria; Sasih Gunalan (Jurnal SASAK : Desain Visual dan Komunikasi, 2020)
This increasingly promising tourism growth is also utilized by the people of NTB, not only in the Mandalika area, NTB tourism has spread widely to remote villages, one of which is in the villages of Sesot, Pakuan, and Buun Sejati, West Lombok which are managed by Pokdarwis Gatari Mass. chaired by Hazudin Nur. The community must be able to compete to become a favorite tourist destination today that is able to attract as many tourists as possible and with this tourism awareness group, another challenge arises, namely, a characteristic that represents Pokdarwis Gatari Mass so that it can give a good impression of the goals, vision and mission achieved. So it takes an intense, quality, and continuous communication that can be used to overcome the challenges that arise. It can be concluded briefly that the logo is able to present as a promotional media for Pokdarwis.